Specific Primers and Nested PCR Find Trichophyton rubrum Missed by Culture of Ground Toenails from Onychomycosis in Podiatric Patients in Eastern Australia - Anjana C. Santosh; Danilla Grando; Ann C. Lawrie (Journal of Fungi, 2025)
Toenail onychomycosis causes significant problems in public health and is more common among the elderly and immune-compromised populations. A previous culture-based survey of communal finely ground toenails from the east coast of Australia isolated 125 T. interdigitale but only one T. rubrum. This paucity of T. rubrum was surprising because it is one of the most common dermatophytes isolated worldwide. Our aim was to find out if T. rubrum was present but not cultured. DNA was extracted from ground toenails from the same samples. New specific primers were designed for the ITS region of T. rubrum that excluded T. interdigitale and vice versa. PCR with these new primers found T. rubrum as well as T. interdigitale in all ground toenail samples. This suggests that T. rubrum was present and common in the ground toenails. It was possibly missed by culture because it grows slowly and was overgrown by T. interdigitale and non-dermatophyte moulds. Alternatively, its viability may have declined earlier, during collection, treatment, or storage of the ground toenails. This has implications for studies of clinical materials, especially nails, as infection by T. rubrum (the most common dermatophyte) may be missed by culture, the main method used in pathology laboratories.